2019
DOI: 10.32839/2304-5809/2019-11-75-207
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and Extralinguistic Properties of Comic Discourse

Abstract: Національний технічний університет України «Київський політехнічний інститут імені Ігоря Сікорського» мОВнІ Та пОзамОВнІ ОСОблиВОСТІ функцІОнуВання кОмІчнОгО ДиСкурСу анотація. Стаття присвячена лінгвістичним та екстралінгвістичним особливостям притаманним англомовному комічному дискурсу. Зважаючи на специфіку англомовного гумористичного виду дискурсу та дослідження, які вже було проведено навколо цього явища, у запропонованій роботі було систематизовано та висвітлено головні мовні та позамовні чинники комічно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The analysis of the literature on the research topic has shown the connection between verbal and paraverbal elements of the text which can be implicit and explicit. Its establishment depends on the linguistic knowledge of the researcher, and it is based on an in-depth analysis of the elements of the text (Marchenko & Marchenko, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The analysis of the literature on the research topic has shown the connection between verbal and paraverbal elements of the text which can be implicit and explicit. Its establishment depends on the linguistic knowledge of the researcher, and it is based on an in-depth analysis of the elements of the text (Marchenko & Marchenko, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%